The main directions for improving tax policy of small and medium businesses - Тулегенова, Р. (Journal of Economic Research & Business Administration, 2017)
This article deals with the basic directions for improvement of tax policy for small and medium-sized businesses. Based on the experience of developed countries, the creation and development of social protection systems, business development, job creation, and competitive environment play an important role in solving social and economic problems. Taxation provides an opportunity to carry out business activities in the state. The effective tax system used by small and medium enterpriceses to reduce dependence on the socio-economic structures. Special tax systems for small and medium-sized businesses, used be taxpayers, developed independently from each other in accordance with the form established by the authorized body of the Republic of Kazakhstan which claim tax policy. The tax accounting policy – document adopted by the taxpayers under the tax legislation. One of the key aspects of fiscal policy in Kazakhstan is the improvement of tax system.